2020
DOI: 10.1017/s0373463319000894
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Versus Traditional Assessment: An Empirical Study Investigating the Difference in Seafarer Students' Academic Achievement

Abstract: Past research showed that traditional assessment methods that required seafarer students to construct responses based on memorisation and analysing information presented in absence of real-world contexts (e.g. oral examinations and multiple-choice questions) disengaged the students from learning. Memorising information is a lower-order cognitive ability, failure in which led to errors and low academic achievement for students. Authentic assessment methods require students to construct responses through the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
2
8
0
2
Order By: Relevance
“…According to Zhang and Zheng (2018), feedback on a student's current ability to perform an assessment task and providing suggestions to improve and to attain their expected levels, encourages the student to take necessary actions to close the gap in their ability. This was confirmed empirically in Ghosh et al (2020). For example, higher academic achievement in AA 2 (student scores improved by 12%) as compared with AA 1 indicated that using the feedback obtained, seafarer students recognised the gaps in their knowledge, re-evaluated their learning approaches and implemented new strategies to improve their scores.…”
Section: Impact Of Feedback Provided To Students On Their Academic Acmentioning
confidence: 58%
See 2 more Smart Citations
“…According to Zhang and Zheng (2018), feedback on a student's current ability to perform an assessment task and providing suggestions to improve and to attain their expected levels, encourages the student to take necessary actions to close the gap in their ability. This was confirmed empirically in Ghosh et al (2020). For example, higher academic achievement in AA 2 (student scores improved by 12%) as compared with AA 1 indicated that using the feedback obtained, seafarer students recognised the gaps in their knowledge, re-evaluated their learning approaches and implemented new strategies to improve their scores.…”
Section: Impact Of Feedback Provided To Students On Their Academic Acmentioning
confidence: 58%
“…This was opposed to a summative traditional assessment that focused on students constructing responses based on memorisation and regurgitation of information. Building on past research findings from Ghosh et al (2020), the authors investigated factors of authentic assessment (task, context, etc.) that correlated significantly to higher academic achievement (measured using scores obtained in the assessment tasks).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mokslininkai akcentuoja, kad naudojama įprasta vertinimo sistema negali pasiekti numatyto tikslo -vertinti žinias ir supratimą nepakanka, jūrininkas turi gebėti kompetentingai elgtis laive (Ghosh, 2018). Imtasi analizuoti tradicinį ir autentišką vertinimus (Ghosh et al, 2020). Išryškėjo, kad tradiciniai vertinimo metodai (egzaminai žodžiu ir klausimai su atsakymų variantais) reikalauja jūrininkų studentų informacijos įsimenamumo gebėjimų, o autentiškas vertinimas skatina kritinį mąstymą, siekiant, kad studentai gebėtų pritaikyti žinias konkrečiame kontekste.…”
Section: Mokymo(si) Turinio Ir Pasiekimų Vertinimo Aspektaiunclassified
“…Australijos jūrų kolegijoje atliktas tyrimas išryškino, kad autentiškai vertinami studentai buvo labiau orientuoti į aukštesnius akademinius pasiekimus, kas leidžia daryti prielaidą, kad akademiniai pasiekimai gerės, jei studentai sutelks dėmesį į informacijos suvokimą, kritinę analizę ir gebėjimą žinias pritaikyti praktikoje, o ne į informacijos įsiminimą. Tyrimo išvados taip pat išryškino, kad itin svarbus tampa grįžtamasis ryšys, kuris turi būti naudojamas nurodant žinių ir įgūdžių spragas, o vėliau labai svarbu suteikti dar vieną galimybę atlikti užduotį prieš priimant galutinį sprendimą dėl studento kompetencijos vertinimo, skatinant savirefleksiją apie dabartinę mokymosi praktiką ir galimybę tobulėti (Ghosh et al, 2020).…”
Section: Mokymo(si) Turinio Ir Pasiekimų Vertinimo Aspektaiunclassified